Packaging Produk Susu Kambing Etawa “Ettakolet” Di Desa Wisata Cikolelet Serang - Chotibul Umam Rina Fitriana (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2019)
This article describes the training activities for packaging etawa goat milk produced by Cikolelet Tourism Village, Serang Regency, Banten. The village's potential and nature in Cikolelet Banten are very rich with agricultural and plantation products and livestock. One of the superior products of the tourist village is etawa goat milk. This goat milk already has a market among residents around tourist villages, unfortunately the packaging is still fairly simple and does not yet have a brand, therefore it is considered less attractive for tourists. The methods used in this community service are observation, interviews, discussions, practice of brand packaging and installation applications, as well as assistance and monitoring evaluation. The subjects of this training were farmers from five etawa goat farms in Cikolelet village. The results of this packaging training activity is the change in product packaging using box-shaped plastic bottles that have been branded to make it more attractive. Packaging and manufacturing of goat's milk product brands succeeded in increasing sales volume by 20% with prices increasing by 25% from the previous selling price. It is expected that this change can make etawa goat milk produced by Cikolelet Village will be better known by the public, as well as favored by tourists.